Trajectory and vibration control of a flexible joint manipulator using interval type-2 fuzzy logic. (November 2019) - Kelekci, Ethem; Kizir, Selcuk
Abstract: This study presents the development of a novel interval type-2 fuzzy logic controller for real time trajectory and vibration control of a flexible joint manipulator. The controller is designed on the Mamdani based interval type-2 fuzzy logic toolbox, which is developed by the authors, using interval triangular membership functions and Karnik–Mendel type reduction algorithm. The closed-loop stability of the system is proved based on Lyapunov stability theorem. In order to observe the effectiveness and robustness of the proposed controller to variations of system parameters (change in link length and payload), the experimental results of interval type-2 and conventional type-1 fuzzy logic controllers are compared. The results show that proposed controller clearly improves the link vibration and trajectory tracking behavior of the system. Highlights: A novel IT2FL-C is proposed for real time control of a flexible joint manipulator. Mamdani based interval type-2 fuzzy logic toolbox is developed. IT2FL-C shows robust control performance against the uncertainties. Stability of the proposed IT2FL-C is analyzed based on Lyapunov stability theorem.